Training with an elastic, supportive bench press device is not superior to a conventional training approach in trained men - Gavanda, S.; Wever, M.; Isenmann, E.; Geisler, S. (German Journal of Exercise and Sport Research, 2021)
The aim of this study was to investigate the effects of an 8-week powerlifting-type bench press (BP) resistance training (RT) program, either without (RAW) or with using a supportive elastic bench press device (EBD) on one-repetition maximum (1-RM), body weight (BW), mid-upper arm and chest circumference, as well as visual analogue pain scale (VAS) of the shoulder, elbow, and wrist. For this purpose, a matched pair parallel design based on initial 1-RM was used (BPD n= 16, age 24.4± 4 years, RT experience 3.75± 1.83 years; RAW n= 16, age 25± 2 years, RT experience 5.66± 3.00 years). Following two weeks of familiarization with the protocol , BP RT was carried out twice weekly. The EBD group completed more than half of their BP sets with elastic assistance and 10% higher training intensity than the RAW group. There was a significant time× group interaction in BW (p= 0.008). Post hoc analysis showed a significant loss of 0.92kg in the EBD group (p= 0.049; effect size [ES]= -0.08; 95%CI [-1.80, 0.04]). A significant time effect for 1-RM was observed (p< 0.001). In both groups there was a significant change in 1-RM of 5.00kg (p< 0.001; ES= 0.35; 95%CI [2.98, 7.02]). There was no significant change in any circumference or VAS measure. In conclusion, using an EBD leads to 1-RM gains similar to conventional RAW BP training. However, more studies are required with highly trained individuals, in particular female athletes. Practitioners may implement EBD training for reasons of variation.